Testicular plasmacytoma misdiagnosed as orchitis. (4th June 2018) - Schiavo, Christopher; Mann, Steven Alexander; Mer, Jesse; Suvannasankha, Attaya
Abstract : Testicular plasmacytomas are rare, accounting for only 1.3% of all extramedullary plasmacytomas. The infrequency in which it is encountered, coupled with its non-specific clinical and sonographic presentation, makes its diagnosis a challenge. We present a case of a 70-year-old man with multiple myeloma, which was systemically responding to chemotherapy, who developed testicular swelling, erythema and pain. Ultrasound findings were concerning for infection, although urine and serum testing were unremarkable. The patient did not improve after several rounds of antibiotics prompting further evaluation. The patient underwent radical orchiectomy which revealed testicular plasmacytoma. Fluorescent in situ hybridisation (FISH) of the testicular tissue noted mutations which had not been present in the FISH analysis of bone marrow. Positron emission tomography scan later revealed new retroperitoneal plasmacytomas involving the new clone and his chemotherapy regimen needed to be adjusted for treatment.